The sustainability indicators of power production systems - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
One of the most important elements of economical and social development is to provide uninterrupted electric energy to consumers. The increasing world population and technological developments rapidly increase the demand on electric energy. In order to meet the increasing demand for sustainable development, it is necessary to use the consumable resources of the world in the most productive manner and minimum level and to keep its negative effects on human health and environment in the lowest level as much as possible. In this study, alignment of hydrogen fuel cells, hydroelectric, wind, solar and geothermal sourced electric energy systems, in addition to fossil fueled coal, natural gas and nuclear power plants, in respect to sustainability parameters such as CO2 emission, land use, energy output, fresh water consumption and environmental and social effects is researched. Consequently, it has been determined that the wind and nuclear energy power plants have the highest sustainability indicators. The fuel cells that use hydrogen obtained by using coal and natural gas are determined as the most disadvantageous transformation technologies in respect to sustainability. This study contains an alignment related to today's technologies. Using of renewable energy resources especially in production of hydrogen, output increases to be ensured with nanotechnology applications in photovoltaic systems may change this alignment. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Alternative energy resources; Sustainability; Availability; External costs; Sera gas emission; Land use; HYDROGEN-PRODUCTION; ENERGY; GENERATION